ONLINE vs. FACE-TO-FACE group coaching to promote teachers mental health: an exploratory field study in German teachers - Sarah S. Lütke Lanfer; Ruth Pfeifer; Yannik Rieder; Alexander Wünsch; Alexander Wünsch; Matthias Braeunig; Claas Lahmann (Frontiers in Digital Health)
IntroductionOnline formats provide promising and low-threshold options for mental health coaching. However, research on online mental health interventions compared to traditional face-to-face interventions remains scarce. In the present study, the established prevention tool “Teacher Group-coaching Program” (TGP) was applied in both the original face-to-face setting as well as online. TGP focuses on promoting mental health in teachers by strengthening relational skills using the Balint group technique. This technique roots back to a psychoanalytic approach to explore the emotional aspects of (stress inducing) professional relationships. The current study aimed at comparing the satisfaction with and effectiveness of TGP between both settings.MethodThe sample consisted of 104 teachers who voluntarily chose between face-to-face (n = 51) and online (n = 53) setting. In a pre-posttest design, participants completed questionnaires before and after the intervention. Additionally participant's satisfaction with the program was assessed during and after TGP.ResultsIntervention effects did not differ significantly in terms of mental health, general life satisfaction and emotional distancing between TGP online and face-to-face. In line with previous research, there was a pre-posttest improvement for mental distress and the ability to distance oneself for both groups, which did not differ significantly between face-to-face and online setting. Satisfaction with the program was rated high in both settings, suggesting similar acceptance.DiscussionAlthough, the absence of an effect is not the evidence of equality of the groups, the present study highlights the potential of online admissions of mental health interventions as possible alternatives and additions to traditional face-to-face programs, especially when in-person meetings are not feasible. Specifically, it shows evidence that the Balint group technique can also be applied successfully by trained experts in the online setting.